Lost in translation: stories told by cross-linguistic onomatopoeias - Cheong, Joy Ningyue (Nanyang Technological University, 2024)
Lost in Translation is an illustrated book that tells stories with onomatopoeias (sound-imitating words) from different languages. This book showcases how onomatopoeias are interpreted by people who don’t speak the languages they are written in. It explores these interpretations, using them to tell stories revolving around each onomatopoeia.